CURRENT STATUS OF THE INDUSTRIAL COMPLEX OF THE SUMY CITY - Корнус, Олеся; Корнус, Анатолій (Human Geography Journal, 2015)
The article provides a description of current state the industry of the Sumy city. The leading branches of industry: mechanical engineering, chemical and pharmaceutical (a pharmaceutical factory, a state biological factory), light industry (textile, clothing and footwear industry) and food (baking, confectionery, alcoholic beverage, brewing, dairy) industry are analyzed and identified. The characteristics (history, production, products and geography of foreign economic relations) of the largest industrial enterprises in the Sumy city are given.